2011
DOI: 10.1002/anie.201101534
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mixed Metal–Organic Frameworks with Metalloligands

Abstract: Immobilization of functional sites within metal-organic frameworks (MOFs) is very important for their ability to recognize small molecules and thus for their functional properties. The metalloligand approach has enabled us to rationally immobilize a variety of different functional sites such as open metal sites, catalytic active metal sites, photoactive metal sites, chiral pore environments, and pores of tunable sizes and curvatures into mixed metal-organic frameworks (M'MOFs). In this Minireview, we highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
172
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(172 citation statements)
references
References 84 publications
0
172
0
Order By: Relevance
“…A different synthetic approach for the preparation of MOFs consists in the use of a ''complex-asligand'' strategy, where a preformed complex acts as a metalloligand. 48 In this approach, a metal complex with vacant additional coordination sites is first prepared and isolated, being used in a second step as a building block towards additional metal ions. 50 The structure consists of an extended parallel array of anionic, oxamato-bridged Mn 4 Cu 6 layers that are further interconnected through two m-phenylene spacers among the Cu II ions (Fig.…”
Section: -47mentioning
confidence: 99%
“…A different synthetic approach for the preparation of MOFs consists in the use of a ''complex-asligand'' strategy, where a preformed complex acts as a metalloligand. 48 In this approach, a metal complex with vacant additional coordination sites is first prepared and isolated, being used in a second step as a building block towards additional metal ions. 50 The structure consists of an extended parallel array of anionic, oxamato-bridged Mn 4 Cu 6 layers that are further interconnected through two m-phenylene spacers among the Cu II ions (Fig.…”
Section: -47mentioning
confidence: 99%
“…15,21 In order to circumvent this problem, it has recently been shown that diluting the extent of functionalisation via a "mixed linker" (ML) approach is effective tuning the stability of the material. [22][23][24][25] Furthermore, varying the composition of mixed linkerMOFs can result in systematic alteration of the gas adsorption capacity and selectivity of the material. Such an approach has been previously been adopted on several MOF topologies, namely MOF-5, 26 MIL-53-Al, [27][28] CAU-10, 29 and MIL-101 30 where a mixture of benzene-1,4-dicarboxylic acid (BDC) and its amino-, bromo-, nitro-, methyl-functionalized derivatives were used as linkers.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the last two decades, a particularly large number of MOFs have been successfully synthesized, [2][3][4][5][6][7] and the versatile characteristics of their chemical moieties have endowed MOFs with many special properties relevant to fuel cell, 8 catalysis 9 and biomedical applications. 10 Because of their ultrahigh porosity and the possibility of functionality, they play an important role in gas adsorption and separation. [11][12][13][14][15] For instance, MOFs are becoming one of the most promising candidates to reduce carbon dioxide (CO 2 ) emissions, which is useful to resolve the increasingly severe global warming problem.…”
Section: Introductionmentioning
confidence: 99%